If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying log(x + 11) + -1log(2) = log(5x + 1) Reorder the terms: glo(11 + x) + -1log(2) = log(5x + 1) (11 * glo + x * glo) + -1log(2) = log(5x + 1) (11glo + glox) + -1log(2) = log(5x + 1) Reorder the terms for easier multiplication: 11glo + glox + -1 * 2glo = log(5x + 1) Multiply -1 * 2 11glo + glox + -2glo = log(5x + 1) Reorder the terms: 11glo + -2glo + glox = log(5x + 1) Combine like terms: 11glo + -2glo = 9glo 9glo + glox = log(5x + 1) Reorder the terms: 9glo + glox = glo(1 + 5x) 9glo + glox = (1 * glo + 5x * glo) 9glo + glox = (1glo + 5glox) Solving 9glo + glox = 1glo + 5glox Solving for variable 'g'. Move all terms containing g to the left, all other terms to the right. Add '-1glo' to each side of the equation. 9glo + -1glo + glox = 1glo + -1glo + 5glox Combine like terms: 9glo + -1glo = 8glo 8glo + glox = 1glo + -1glo + 5glox Combine like terms: 1glo + -1glo = 0 8glo + glox = 0 + 5glox 8glo + glox = 5glox Add '-5glox' to each side of the equation. 8glo + glox + -5glox = 5glox + -5glox Combine like terms: glox + -5glox = -4glox 8glo + -4glox = 5glox + -5glox Combine like terms: 5glox + -5glox = 0 8glo + -4glox = 0 Factor out the Greatest Common Factor (GCF), '4glo'. 4glo(2 + -1x) = 0 Ignore the factor 4.Subproblem 1
Set the factor 'glo' equal to zero and attempt to solve: Simplifying glo = 0 Solving glo = 0 Move all terms containing g to the left, all other terms to the right. Simplifying glo = 0 The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined.Subproblem 2
Set the factor '(2 + -1x)' equal to zero and attempt to solve: Simplifying 2 + -1x = 0 Solving 2 + -1x = 0 Move all terms containing g to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + -1x = 0 + -2 Combine like terms: 2 + -2 = 0 0 + -1x = 0 + -2 -1x = 0 + -2 Combine like terms: 0 + -2 = -2 -1x = -2 Add 'x' to each side of the equation. -1x + x = -2 + x Combine like terms: -1x + x = 0 0 = -2 + x Simplifying 0 = -2 + x The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined. The solution to this equation could not be determined.
| 21=-7u | | 18+5=20+1 | | 2/3x-16 | | (x/4)=3 | | 3y=8-7y-1 | | (12b-6)-(7-18b)= | | (2n^2+4n+3)(2n-3)= | | (-7x)(-1/7) | | 76.9-34.782= | | 8x+3.5=36 | | 6-10=1 | | 16x^2+7x-9=0 | | 3(1+2y)-5=6y-2 | | .468*4.8= | | -14.49-3.9d=3.3(d+3.9) | | 5=3n-n+5 | | 576*.6= | | -2x^2+20x=-82 | | a^2-4a-24+6a= | | 3(1-2y)-5=6y-2 | | 2a-10=44+8a | | -2d+18-4b=60 | | 9x+2+5x+4= | | 4x^2=488 | | (x-30)*.5=100 | | -6(1a-2b)-2(5b-4a)= | | -.25x+6=.5x+3 | | y-35=4.7 | | 7x+7+5x+6= | | 4(x+2)-3x+5=x+5 | | x^2+18x=-32 | | 10x+7+4x+7= |